Manajemen Tenaga Pendidik Dan Tenaga Kependidikan - Sukatin Sukatin; Feni Dwita Kristi; Jihan Nabila Putri; Gilang Anjari (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Managemen of teaching staff and education staff is a complex and strategic process to improve the quality of education.In this context,the managemen of teaching and educational staff focuses on the effective and efficient development,managemen and use of human resources.In this way,the managemen of teaching staff and educational staff can improve the quality of educational,increase teacher motivation and job satisfaction,and improve the quality of educational services provided. In the managemen of teaching staff and educational sataff,several important factors that need to be considered are the development of teacher competency,time and resource management,and the use of technology to increase efficiency and effectiveness.Apart from that,management of teaching staff must also pay attetion to other aspects such as organizational culture,commonication and teacher job satisfaction.Thus,management of teaching staff and educational staff can be an effective strategy for improving the quality of education and increasing student achievement.